O COMUNISMO HISTÓRICO: IDÉIA DE REVOLUÇÃO NO SÉCULO XX - Lincoln Secco (Dialogos, 2017)
O artigo analisa a experiência do “comunismo histórico” no mundodurante o século XX. São acompanhadas as várias fases dessa experiência(ascensão, declínio, recuperação e decadência) e os múltiplos desafios e problemas enfrentados pelos comunistas neste século. A problemática eleitoral e o relacionamento com os socialistas são especialmente enfatizadas.Abstract. The article analyzes the experience of “historical communism” in the world during the 20th century. The different stages of that experience (rise, fall, recovery and decline) are monitored, as well as the multiple challenges and problems faced by communists in this century. The problem of elections and the relationship with socialists are particularly emphasized.